A single magnetic field exposure system for sequential investigation of real time and downstream cellular responses - Rao, Raj R.; Kisaalita, William S. (Bioelectromagnetics, 2004)
To be able to correlate real time membrane potential or ion flux changes with further downstream gene transcription responses due to extremely low frequency (ELF) electromagnetic field (EMF) exposure, we devised an experimental system consisting of a pair of symmetric circular coils. This system can be used on an inverted microscope stage (real time signaling) as well as inside controlled environment incubators (gene transcription end points). The system includes a unique, custom made switch box for blinding the experimental staff and a power amplifier. We report herein the design and characterization of the system with respect to parameters considered important in in vitro ELF–EMF exposure studies, including linear magnetic field distribution, compensation for microscope objective lens interference, heating effects of the coils, and harmonic content of the signals. Bioelectromagnetics 25:27–32, 2004. © 2003 Wiley-Liss, Inc.